Antibacterial activities of lactic acid bacteria isolated from cow faeces against potential enteric pathogens - Adeniyi, Bolanle A (Afr Health Sci, 2015)
BACKGROUND: The addition of sub therapeutic doses of antibiotics to cattle feed for growth promotion is a contributory factor to antibiotic resistance, thus an alternative to antibiotics is needed in animal feed additives. OBJECTIVE: To determine the antimicrobial activity of cow's intestinal Lactic acid bacteria (LAB) against enteric commensals. METHOD: Escherichia coli, Klebsiella species (spp) and LAB were isolated from thirty different cow faecal samples and the LAB identified by partial sequencing of 16S rRNA. The antimicrobial activity of the LAB was determined against the test Escherichia coli and Klebsiella spp. RESULTS: Five species of LAB were isolated from thirty cow faecal samples and identified as Enterococcus hirae (8), Enterococcus durans (6), Enterococcus faecium (1), Enterococcus faecalis (1) and Weissella confusa (1). Viable cells and cell free supernatant (CFS) of the LAB were able to inhibit the growth of the test organisms with the largest zone of inhibition by the viable cells being 26mm against Escherichia coli CB6 produced by Enterococcus hirae CO6A while Weissella confusa CO29M and Enterococcus hirae CO2A produced the largest zones of inhibition (26mm) against Klebsiella CB2. CONCLUSION: This study shows that LAB from cow faeces possess considerable antimicrobial activity against resistant Escherichia coli from the same environment.